2015
DOI: 10.18632/oncotarget.5643
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the ROR1 and ROR2 receptors in epithelial ovarian cancer inhibits cell migration and invasion

Abstract: AIMIn recent years, the Wnt signalling pathway has been implicated in epithelial ovarian cancer and its members have potential as diagnostic, prognostic and therapeutic targets. Here we investigated the role of two Wnt receptor tyrosine kinases (RTKs), ROR1 and ROR2, and their putative ligand, Wnt5a, in ovarian cancer.METHODSImmunohistochemistry for ROR2 was performed in a large patient cohort, including benign controls, borderline tumours and epithelial ovarian cancer. In addition, siRNA was used to silence R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(98 citation statements)
references
References 32 publications
(45 reference statements)
7
90
1
Order By: Relevance
“…In contrast, studies involving a large number of patients found that upregulation of Wnt5a was associated with a relatively poor prognosis [5458]. Compared with the frequency of Wnt1 expression in ovarian cancer, Wnt5a was more frequently found in malignant epithelial ovarian cancer patients (80% out of a total 38) [54].…”
Section: Wnt5a Signaling In Ovarian Cancer Stem Cellsmentioning
confidence: 99%
“…In contrast, studies involving a large number of patients found that upregulation of Wnt5a was associated with a relatively poor prognosis [5458]. Compared with the frequency of Wnt1 expression in ovarian cancer, Wnt5a was more frequently found in malignant epithelial ovarian cancer patients (80% out of a total 38) [54].…”
Section: Wnt5a Signaling In Ovarian Cancer Stem Cellsmentioning
confidence: 99%
“…It is recognized that ROR1 and ROR2 expression diminishes in adult tissue [27], with many studies indicating increased expression associated with malignant progression [3], [4], [10], [11], [12], [28], [29], [30]. We have previously found ROR2 and its receptor, WNT5A, to be upregulated in OC [13], [31], [32] patient samples and have shown in vitro that both ROR1 and ROR2 are important in OC migration and invasion, indicating a role in OC metastasis [32]. However, it is unknown how the receptors interplay, and therefore, we aimed to analyze the expression of both receptors in the same cohort.…”
Section: Resultsmentioning
confidence: 95%
“…In many cases, the receptor tyrosine kinases ROR1 and ROR2 are abnormally overexpressed in tumors and associated with stem cell properties, epithelial to mesenchymal transition, and metastasis [2], [3], [4], [5], [6], [7], [8], [9], [10], [11], [12]. In OC, we have previously shown that both ROR1 and ROR2 are important in cell growth, migration, and invasion [13]. Others have confirmed the role of ROR1 in OC and have found that inhibiting ROR1 using a monoclonal antibody halts the growth of tumor xenografts [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…Yes (127) Yes (128) Breast cancer (86,87) ; melanoma (92,94) ; non-small cell lung cancer (129) ; gastric cancer (130) ; ovarian cancer (131) …”
Section: Ror1mentioning
confidence: 99%
“…Yes (19,127,132) Yes (48,133) Breast cancer (81) ; prostate cancer (41) ; melanoma (90,92) ; non-small cell lung cancer (134) ; colorectal cancer (135) ; gastric cancer (136) ; ovarian cancer (131) …”
Section: Ror2mentioning
confidence: 99%